NHLRC1 repeat expansion in two beagles with Lafora disease1. (16th October 2016) - Hajek, I.; Kettner, F.; Simerdova, V.; Rusbridge, C.; Wang, P.; Minassian, B. A.; Palus, V.
Abstract : Lafora disease is a fatal genetic disorder characterised by neurotoxic deposits of malformed insoluble glycogen. In humans it is caused by mutation in the EPM2A or NHLRC1 genes. There is a known mutation in miniature wirehaired dachshunds which has not been documented in other dog breeds, including beagles, in which the disease is relatively commonly reported. This case report describes the causative defect in two affected beagles, namely the same massive expansion as in miniature wirehaired dachshunds of a 12‐nucleotide repeat sequence that is unique to the canine NHLRC1 gene. This is the first mutation described in beagles with Lafora disease, and so far the only Lafora disease genetic variant in dogs.